Pricing sovereign credit risk of an emerging market - Gonzalo Camba-Méndez; Konrad Kostrzewa; Anna Marszal; Dobromil Serwa (European Central Bank (ECB), 2016)
We analyze the market assessment of sovereign credit risk in an emerging market using a reduced-form model to price the credit default swap (CDS) spreads thus enabling us to derive values for the probability of default (PD) and loss given default (LGD) from the quotes of sovereign CDS contracts. We compare different specifications of the models allowing for both fixed and time varying LGD, and we use these values to analyze the sovereign credit risk of Polish debt throughout the recent global financial crisis. Our results suggest the presence of a low LGD and a relatively high PD for Poland during the crisis. The highest PD is in the months following the collapse of Lehman Brothers. The derived measures of sovereign risk are strongly linked with the level of public debt and with another measure of PD from a structural model. Correlations between our PD values and the CDS spreads heavily depend on the maturity of the sovereign CDS.
Keywords: C11; C32; G01; G12; G15; 330; CDS spreads; loss given default; Poland; probability of default; sovereign credit risk